THE FUNCTION OF DIGITAL SKILLS AMONG EMPLOYEES THAT LEADS TO INNOVATIVE WORK BEHAVIOR - Khalijah binti Mohd Nor; Aliah Faqihah binti Azhar; Nisrin Izzati binti Roslan; Nurfarah Syafiqah binti Mahat; Nurhazirah Nisa binti Asmadie; Nurhidayah binti Samudi (International Journal of Accounting, Finance and Business, 2022)
This paper aimed to discuss about the function of digital skills among employees that leads to innovative work behavior. The current study involves a reviewed research articles which were gathered from various articles which are Scopus, Science Direct, ACM Digital Library and Emerald Insight databases. A total of 20 articles have been reviewed from the year 2017 to 2022. This study has been classified into digital skills and employee creativity, followed by innovative work behaviour. It was observed that digital skills have a lot of diversity. The finding reveals how employees’ creativity can be influenced by digital skills and the occurrence of innovative work behaviours among employees. This paper also helps to understand the conceptual knowledge of digital skills, employee creativity, and how it will affect employee’s performance in organization. Currently, we are seeing exponential growth of innovations and technology applications across all parts of the economy and our lives due to a multitude of variables relating to both technology and human factors. One of the most noticeable characteristics of the digitally transformed world is that it necessitates ongoing changes in industry and research, as well as the advancement of multidisciplinary solutions to strengthen the employee’s creativity and innovative work behaviour. A total of 20 research articles on digital skills and innovative work behavior were reviewed. Moreover, this paper will show how to strengthen employees creativityy using digital skills.